ENTRE A LEMBRANÇA E O ESQUECIMENTO: OS TRABALHOS DA MEMÓRIA NA RELAÇÃO COM LÍNGUA E DISCURSO - De Nardi, Fabiele Stockmans (Organon, 2003)
Our task in this work is an attempt to understand some of therelations that are established between tongue, discourse and memory, basedon what the discourse theory proposes,. We will provide, for this purpose,a brief theoretical explanation, working with the construction and functioningof these concepts, in order to specify their contour and reflect abouttheir inter-relation. Passing through the real language, treating it as amateriality that feeds the discursive process, we will seek for the discourse,place for the production of senses and memory game. To conclude wepropose a brief reflection about the effects of the assumption of the conceptsof the discourse analysis to the work of the second language teaching.